AERODYNAMIC ANALYSIS OF SPORT UTILITY VEHICLE (SUV) BY COMPUTATIONAL FLUID DYNAMICS (CFD) APROACH - Junaidin, Buyung (Institut Teknologi Dirgantara Adisutjipto, 2022)
The main purpose of aerodynamics analysis of a vehicle is optimizing it’s form to increase aerodynamics efficiency. More streamline of aerodynamic design of a vehicle not just effecting to lower fuel consumption which is cause by lower drag due to wind at highspeed, but also increasing stability dan control of the vehicle itself. The vehicles are existed with many variations of form so they have difference aerodynamic characteristics. For a personal vehicle like cars, have many variants such as sedan, sport utility vehicle (SUV), multipurposes utility vehicle (MPV), ect. It becomes a motivation to do research about aerodynamic analysis of a SUV car which is a car variant with huge utilize in Indonesia. In this research, aerodynamic characteristics of SUV car are evaluated by computational simulation with computational fluid dynamics (CFD) approach. CFD simulation yields aerodynamic characteristics data and flow behaviors around car model. Simulation results show that critical drag coefficient (CDcrit) of SUV car is 0.36 with lift coefficient is 0.25. the CDcrit of the car is lower than typical value for a modern car. So that, optimalization of SUV car form which analyzed is needed. Contours of pressure at car surfaces show that high pressure area are located at front of grill and windshield, and low-pressure area are located at nose and leading-trailing roof due to the form nose and leading-trailing roof are streamlines. At back surface of the car, low pressure area are formed by flow separation which creates wake.